Computational analysis of a semi-industrial furnace fired by a flat flame burner under different O2/N2 ratios using the steady laminar flamelet approach. Issue 4 (August 2017) - Mayr, B.; Prieler, R.; Demuth, M.; Potesser, M.; Hochenauer, C.
Abstract: This paper uses computational fluid dynamics (CFD) to investigates a natural gas fired semi-industrial furnace with a thermal input of 250 kW which operates under different O 2 / N 2 ratios in the oxidizer. The furnace is fired by a flat flame burner which is commonly used in industrial furnaces. The simulations were confronted with temperature measurements inside the furnace and with measurements of the surface temperature of the quarl. The main focus was on using models which are not computationally demanding. The steady laminar flamelet model (SFM) with a detailed mechanism was thus used to model the combustion. With the SFM the calculation time can be dramatically reduced compared to simulations with the eddy dissipation model (EDM) although using a detailed mechanism. The skeletal25 mechanism, consisting of 17 species and 25 reactions, was used in this investigation. Additionally the furnace was simulated with the two detailed mechanism GRI 3.0 and smooke46. The predicated temperature inside the furnace of the SFM and the skeletal25 were in good accordance with the measurements for all oxygen concentrations in the oxidizer. The predicted surface temperature of the quarl showed higher deviation from the measurements but also showed a reasonable standard of accuracy. Furthermore the investigation demonstrated that the two detailed mechanisms GRI 3.0 and smooke46 are also applicable for flat flame burners and oxygen concentrations up to 37 Vol% oxygen in the oxidizer, a finding which is in contrast to previous investigations with jet flames. For oxygen concentrations higher than 37 Vol% in the oxidizer the GRI 3.0 and the smooke46 mechanisms fails to predict the temperature field in the furnace. Only the skeletal25 mechanism was able to predict the temperature field correct for higher oxygen concentrations in the oxidizer. Highlights: CFD modelling of an 250 kW semi-industrial furnace fired by a flat flame burner. Time saving combustion modelling using the steady flamelet model. Comparison of different detailed reaction mechanism for different oxygen enrichments in the oxidizer. Comparison between CFD and measurements.